2011
DOI: 10.5089/9781455264452.001
|View full text |Cite
|
Sign up to set email alerts
|

Global Liquidity: Availability of Funds for Safe and Risky Assets

Abstract: What is global liquidity and how does it affect an economy? The paper addresses that question by looking at liquidity from two different perspectives: global liquidity as availability of funds in safe and risky asset markets. This distinction between safe and risky asset markets is important due to market segmentation, which called for unconventional monetary policy to restore a function of risky asset markets. To analyze the effect of global liquidity, I construct proxy variables and then asses how they affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 30 publications
0
20
0
2
Order By: Relevance
“…(seasonally adjusted) plus total foreign exchange reserves excluding gold (Chinn, 2011;Matsumoto, 2011) Further variables included in the empirical analysis are nominal GDP (Y_G) and the consumer price index CPI (CPI_G) on a global level. We also include the nominal effective exchange rate of the US dollar (USD_EER) to account for dollar valuation effects, and data on exports of emerging and developing economies (EX_EC) 12 to the rest of the world as proxies for demand driven impulses for the development of commodity and food prices, which are represented by indices of the Commodity Research Bureau (CRB).…”
Section: Data Description and Aggregation Of The International Liquidmentioning
confidence: 99%
“…(seasonally adjusted) plus total foreign exchange reserves excluding gold (Chinn, 2011;Matsumoto, 2011) Further variables included in the empirical analysis are nominal GDP (Y_G) and the consumer price index CPI (CPI_G) on a global level. We also include the nominal effective exchange rate of the US dollar (USD_EER) to account for dollar valuation effects, and data on exports of emerging and developing economies (EX_EC) 12 to the rest of the world as proxies for demand driven impulses for the development of commodity and food prices, which are represented by indices of the Commodity Research Bureau (CRB).…”
Section: Data Description and Aggregation Of The International Liquidmentioning
confidence: 99%
“…Indeed, Favero and Giavazzi (2008), among others, have shown that the Eurozone economies are deeply affected by global conditions and Andritzky (2012) argues that the strong increase in global risk aversion following the subprime financial crisis may have pushed foreign investors to retract from advanced financial markets. In addition, the inclusion of the VIX variable in the SVAR enables to control for time variations related to the global crisis period, as it proxies uncertainty and global liquidity (Matsumoto, 2015).…”
Section: Empirical Testsmentioning
confidence: 99%
“…Neumeyer and Perri (2005) is an early paper showing that sovereign spreads in EMEs behave in a countercyclical manner, which is what subsequent work shows. 5 The effect of global risk aversion on EMEs' economic fluctuations have also been highlighted by Matsumoto (2011) and Carrière-Swallow and Céspedes (2013); although, these papers are silent on its effect on country spreads. On the effects of global factors on EMEs' sovereign spreads, Arora and Cerisola (2001), González-Rozada and Levy-Yeyati (2008), and Ciarlone et al (2009) show that EMEs' sovereign spreads depend negatively on global financial conditions, such as U.S. interest rates, U.S. high-yield corporate spreads, and the volatility of U.S. stock prices, respectively.…”
Section: Introductionmentioning
confidence: 99%